Pendidikan Etika Kristen: Menanamkan Kasih, Pengampunan, Keadilan, dan Kebenaran dalam Kehidupan Manusia - Yohana Nelly P; Edward C. P. Pardede; Humiras Pakpahan; Jecson P. Sihombing; Saktina M. Simanullang (Jurnal Pendidikan dan Sastra Inggris, 2025)
This article discusses the role of Christian Ethics Education in instilling the values of love, forgiveness, justice, and truth as moral and spiritual foundations in modern human life. Amid the moral crisis and value shifts caused by globalization and technological advancement, Christian education is viewed as having a transformative function in shaping character rooted in the love of Christ. This study employs a qualitative approach using library research methods, analyzing various theological and contemporary educational literatures. The findings indicate that love serves as the central principle of Christian ethics, guiding humanity to live in relationships characterized by compassion and respect; forgiveness opens the way for reconciliation and the restoration of relationships; justice reflects the image of a righteous God who upholds equality; while truth fosters integrity and a life aligned with God’s will. Therefore, Christian Ethics Education is not merely the transfer of knowledge but the holistic formation of character through contextual and practical faith learning. Its implementation in schools, churches, and families is expected to produce a generation of believers who embody the character of Christ and serve as agents of peace and truth in a constantly changing world.